2006
DOI: 10.1002/bip.20478
|View full text |Cite
|
Sign up to set email alerts
|

HFIP‐induced structures and assemblies of the peptides from the transmembrane domain 4 of membrane protein Nramp1

Abstract: Membrane protein Nramp1 (natural resistance-associated macrophage protein 1) is a pH-dependent divalent metal cation transporter that regulates macrophage activation in infectious and autoimmune diseases. A naturally occurring glycine to aspartic acid substitution at position 169 (G169D) within the transmembrane domain 4 (TM4) of Nramp1 makes mice susceptible to Leishmania donovani, Salmonella typhimurium, and Mycobacterium bovis. Here we present a structural and self-assembling study on two synthetic 24-resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 43 publications
0
16
1
Order By: Relevance
“…In contrast, the molar ellipticity of the R9AP-Cter peptide is much smaller in HFIP than in HMeOH (Fig. 2G), which is not consistent with previous observations that this solvent favors the formation of α-helical structures (see section 3.1) [89][90][91][92][93][94][95][96][97][98][99][100][101][102][103].…”
Section: Circular Dichroism and Infrared Spectroscopy Of The Hydrophocontrasting
confidence: 70%
See 2 more Smart Citations
“…In contrast, the molar ellipticity of the R9AP-Cter peptide is much smaller in HFIP than in HMeOH (Fig. 2G), which is not consistent with previous observations that this solvent favors the formation of α-helical structures (see section 3.1) [89][90][91][92][93][94][95][96][97][98][99][100][101][102][103].…”
Section: Circular Dichroism and Infrared Spectroscopy Of The Hydrophocontrasting
confidence: 70%
“…Nevertheless, care must be taken when using TFE and HFIP because it is generally believed that they enhance the population of helical conformations of peptides and proteins. In particular, since the pioneering work of Tamburro et al [88], fluorinated alcohols, such as TFE and HFIP, have been shown to promote the formation of α-helices for a large number of proteins and peptides (see, for example, references [89][90][91][92][93][94][95][96][97][98][99][100][101][102][103] and the references cited therein). It has been proposed that fluoroalcohol complexes would displace water molecules from the surface of the peptide; the acidity or hydrogen-bonding ability and hydrophobicity of the fluoroalcohols appear to play an important role [104].…”
Section: The Challenge Of Solubilizing Hydrophobic Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, while organic solvents are frequently used in structural studies on single, monomeric peptides, they are widely considered unsuitable for investigations of helix-helix interactions and peptide oligomerization. Using diffusion-ordered spectroscopy (DOSY) NMR, however, Sun and coworkers discovered peptide oligomers even in 100% TFE Xue et al, 2008Xue et al, , 2009 or 40% HFIP (Li et al, ,c, 2008Xue et al, 2006). The authors determined high-resolution structures of oligomers composed of peptides corresponding to TM helix 4 of solute carrier family 11 member 2 (Slc11a2, formerly known as divalent metal transporter 1 (DMT1)) and TM helix 4 of the homologous protein Slc11a1 (formerly known as natural resistance-associated macrophage protein 1 (Nramp1)).…”
Section: Influence On Helix-helix Interactions In Solute Carrier Famimentioning
confidence: 97%
“…Even if more convincing evidence of peptide oligomers in SDS micelles can be found, it still remains to be shown that they possess pore activity. To settle the uncertainties surrounding Slc11a2 TM helix 4, and a similar case involving TM helix 4 of Slc11a1 (Xue et al, 2006(Xue et al, , 2008(Xue et al, , 2009, further experiments are urgently needed.…”
Section: Oligomerization Of Tm Helix 4 Of Solute Carrier Family 11 Mementioning
confidence: 99%